Digital Bureaucracy, Transparency, and Public Trust in Government A Systematic Literature Review - Diana Diana; Fajar Apriani; Rungarun Boonsayan (Faculty of Social and Political Siences Universitas 17 Agustus 1945 Samarinda, 2026)
The study examines the growing role of digital bureaucracy in transforming public administration by enhancing efficiency, transparency, and public trust. The purpose of the research is to analyze how digital tools, such as e-government platforms, AI, and data analytics, have reshaped bureaucratic systems and their relationship with citizens. A systematic literature review methodology was employed, reviewing studies that assess the integration of digital technologies in government operations. The findings reveal that while digital transformation significantly improves service delivery and transparency, it also introduces challenges, such as the digital divide and concerns over data privacy and security. Digital platforms, by making government processes more accessible, foster greater public trust, yet these tools must be inclusive and secure to prevent alienating marginalized groups. The research suggests that governments need to address digital exclusion through investments in infrastructure and digital literacy programs, and prioritize data protection measures to maintain public trust. The implications of this study are far-reaching, urging policymakers to ensure the equitable distribution of digital services and the ethical use of technology, which is crucial for fostering a well-informed, engaged, and trustful relationship between the government and citizens.